Translation Quality Assessment of the Analysis of Deixis Made by Indonesian EFL Undergraduate Students Abstract - Simanjuntak, Faido Marudut Pardamean (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the translation quality in terms of accuracy, acceptability, and readability of the translated text of the abstract titled